2015
DOI: 10.1021/acsnano.5b05113
|View full text |Cite
|
Sign up to set email alerts
|

A Colorimetric Plasmonic Nanosensor for Dosimetry of Therapeutic Levels of Ionizing Radiation

Abstract: Modern radiation therapy using highly automated linear accelerators is a complex process that maximizes doses to tumors and minimizes incident dose to normal tissues. Dosimeters can help determine the radiation dose delivered to target diseased tissue while minimizing damage to surrounding healthy tissue. However, existing dosimeters can be complex to fabricate, expensive, and cumbersome to operate. Here, we demonstrate studies of a liquid phase, visually evaluated plasmonic nanosensor that detects radiation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Therefore, there is a need to independently verify the radiation dose delivered to the patient to ensure patient safety and improve the quality of life posttreatment. (Pushpavanam, Narayanan, Chang, Sapareto, & Rege, ). Facile radiation sensors that are easy to fabricate, operate and read would enable clinicians and physicists to verify the radiation dose independently and assist in decision making for future irradiations administered to the patient; however, current dosimeters are insufficient for many routine clinical applications due to their inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to independently verify the radiation dose delivered to the patient to ensure patient safety and improve the quality of life posttreatment. (Pushpavanam, Narayanan, Chang, Sapareto, & Rege, ). Facile radiation sensors that are easy to fabricate, operate and read would enable clinicians and physicists to verify the radiation dose independently and assist in decision making for future irradiations administered to the patient; however, current dosimeters are insufficient for many routine clinical applications due to their inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a gold‐alanine nanocomposite has been evaluated as a radiation dosimeter but the requirement of a sophisticated readout technique like electron paramagnetic resonance has prevented its clinical translation (Guidelli, Ramos, Zaniquelli, Nicolucci, & Baffa, ). To mitigate these concerns, a colorimetric sensor based on the formation of gold nanoparticles as a response to therapeutic levels of ionizing radiation was demonstrated (Sahil Inamdar et al, ; Pushpavanam et al, ). The intensity of color was proportional to the intensity of irradiation and was used as a measure of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is holding great promise for diseases diagnosis, targeted delivery of drugs, and biosensors 15–17 . Recently, it has been demonstrated that proteins bind to the surface of nanoparticles when nanomaterials are introduced to biological fluids, to form clouds of adsorbed proteins known as ‘protein corona’ 18–19 .…”
Section: Introductionmentioning
confidence: 99%
“…The detection range can also be expanded to 5–37 Gy through modulating the concentration and chemistry of the templating liquid surfactant. With the help of this nanosensor, the qualitative detection of radiation can be observed by naked eye, and the quantitative radiation dose can be analyzed by an absorbance spectrophotometer (Pushpavanam et al 2015). …”
Section: Application Of Nanotechnology To Image-guided Radiotherapymentioning
confidence: 99%